2013
DOI: 10.1371/journal.pone.0083517
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-Binding Lectin Inhibits Candida albicans-Induced Cellular Responses in PMA-Activated THP-1 Cells through Toll-Like Receptor 2 and Toll-Like Receptor 4

Abstract: Background Candida albicans (C. albicans), the most common human fungal pathogen, can cause fatal systemic infections under certain circumstances. Mannan-binding lectin (MBL),a member of the collectin family in the C-type lectin superfamily, is an important serum component associated with innate immunity. Toll-like receptors (TLRs) are expressed extensively, and have been shown to be involved in C. albicans-induced cellular responses. We first examined whether MBL modulated heat-killed (HK) C. albicans-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…To further elucidate the actions of CMPs as TLR4 ligands in the HEK-TLR4 model we measured inflammatory gene transcripts that are typically produced in phagocytic cell lines stimulated with C . albicans [ 41 ] or mannose-based PAMPs [ 42 ]. Given the manufacturer’s recommended assay time course and reduced cell density requirements (0.5–1 x 10 5 cells/ml) for the reporter cell assays, initial cytokine ELISAs were unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
“…To further elucidate the actions of CMPs as TLR4 ligands in the HEK-TLR4 model we measured inflammatory gene transcripts that are typically produced in phagocytic cell lines stimulated with C . albicans [ 41 ] or mannose-based PAMPs [ 42 ]. Given the manufacturer’s recommended assay time course and reduced cell density requirements (0.5–1 x 10 5 cells/ml) for the reporter cell assays, initial cytokine ELISAs were unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
“…MBL by interaction with Toll-like receptor TLR-2 or TLR-4, inhibits C. albicans-induced interleukin (IL)-8 and tumor necrosis factora production from THP-1 cells. 17 The question is whether circulating MBL comes only from the liver and exerts an opsonization effect by eliminating fungal infection/colonization or whether MBL is also produced and released locally in the GI tract itself after fungal challenge. In the present study, we explored the expression of MBL in the gut epithelium and examined its impact on modulation of intestinal inflammation and C. albicans elimination.…”
Section: Introductionmentioning
confidence: 99%
“…THP-1 cells differentiate into macrophages and express their particular ratios of different FcgR isotypes by PMA activation (20,21). The THP-1 cells used in the present study expressed FcgRI, FcgRII and FcgRIII, as shown by flow cytometry with mAbs against those individual receptors (Fig.…”
Section: Discussionmentioning
confidence: 64%